The need to generate realistic strain signals at an automotive coil spring for durability simulation leading to fatigue life assessment. (15th September 2017) - Putra, T.E.; Abdullah, S.; Schramm, D.; Nuawi, M.Z.; Bruckmann, T.
Highlights: Simulated strain signals were developed in the current study. Applying the wavelet transform, the simulated strain signals were shorter than before. In order to validate the strain data, fatigue tests were performed showing the reduction of time. Abstract: This study aims to accelerate fatigue tests using simulated strain signals. Strain signals were acquired from a coil spring involving car movements. Using a mathematical expression, the measured strain signals yielded acceleration signals, and were considered as disturbances on generating strain signals. The simulated strain signals gave the testing time deviation by only 1.5%. The wavelet-based data editing was applied to shorten the strain signals time up to 36.7% and reduced the testing time up to 33.9%. In conclusion, the simulated strain signals were able to maintain the majority of fatigue damage and decreased the testing time.